Median cleft of mandible and lower lip with ankyloglossia and ectopic minor salivary gland on tongue - Rana, Roshani E.; Puri, Vinita A.; Thakkur, Rahul K.; Baliarsing, A. S. (Indian Journal of Plastic Surgery, 2004)
Median cleft of lower lip and mandible is a rare anomaly. This Cleft has also been described as Cleft No. 30 of Tessier's classification. In minor forms only lower lip is cleft. Frequently, the cleft extends into the mandibular symphysis and the tongue is attached to the cleft alveolar margin. At times the tongue may be bifid or absent, hyoid absent, thyroid cartilage underdeveloped, strap muscles atrophic, manubrium sterni absent, clavicles widely spaced etc. The earliest report of this anomaly was by Couronne' in 1819. Since then very few cases have been reported in literature with variations. We describe a male child who presented at the age of 6 months with an ectopic salivary gland on the dorsum of the tongue in addition to median cleft of lower lip, ankyloglossia and notching of the mandible. Excision of mass on dorsum of tongue, release of ankyloglossia and lip from the alveolus followed by repair was done. No bony work was done since the mandible was only notched. On post-operative follow-up at 18 months, dentition was delayed in both maxillary as well as mandibular teeth and there was a gap between the lower central incisors. At the age of 2 years 4 months, the dentition is still not complete and the gap between the lower central incisors is very apparent. There is a supernumerary upper central incisor on right side. There is no mobility between the two segments of mandible. Speech is normal. A regular follow-up will be done to study the eruption of permanent central incisors at the age of 7 years and till eruption of all permanent teeth to assess the occlusion and to decide whether any bony work is needed or not.
Keywords: Median cleft mandible; Median cleft lower lip; Tessier cleft 30